Faktor-Faktor Yang Mempengaruhi Financial Sustainability Ratio (FSR) - Putra Prasetya, Bangun; Iga Ratnasari, Arum (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Islam Majapahit, 2024)
Perumda BPR Bank Jogja is a corporation of Yogyakarta city that supports and encourages the growth of regional economic development as well as regional capital sources that improve the standard of living and welfare of the community. So that financial sustainability is important related to the sustainability of Perumda BPR Bank Jogja in its financial aspect. This study uses independent variables, namely Non Performing Loan (NPL), Return on Asset (ROA) with dependent variables Financial Sustainability. The purpose of this study is to see the effect of Non-Performing Loan (NPL), Return on Asset (ROA) on Financial Sustainability. This research uses the research object of Perumda BPR Bank Jogja which has a mission to realize public welfare in the financial sector. Data is obtained from financial statements. The results showed that the t test on the Non-Performing Loan (NPL) variable was 0.575 and Return On Asset (ROA) was 0.017. The results of the t-test show a significance value of 0.268. The results can be concluded that Non-Performing Loan (NPL) has no effect while Return On Asset (ROA) has an effect. Based on test F, Non-Performing Loan (NPL) and Return On Asset (ROA) have a significant impact on the Financial Sustainability Ratio (FSR).